Aprendizagens em percepção musical: um estudo de caso com alunos de um curso superior de música popular - Darcy Alcantara Neto (2010)
This research is about the learning processes related to musical perception of 13 students who were admitted in the Bachelor of Popular Music at the Music School of the Federal University of Minas Gerais, in the year of 2010. The goal is to understand how such students built their knowledge and skills related to musical perception prior to college and what meanings and values they attribute to them, in addition to investigating conflicts experienced during the acquisition processes, impacts of these on their musical practices and expectations about the aural training classes at the university. The qualitative research used the instrumental case study approach and used questionnaires and focus groups. Impacts of the aural training classes were detected on listening, creativity and musical preferences of the students; in turn, the meanings they attribute to classes differ, legitimating or challenging prevailing social representations. Research suggests, finally, that the assessment of knowledge and skills related to aural training classes can be interpreted as a mechanism of exclusion and barrier of access to higher education.